IMPLEMENTASI KEGIATAN MUHADHARAH DALAM MENINGKATKAN BAKAT SANTRI DI PONPES MADINATUL MUNAWWARAH - Juwita Optalia; Bambang Trisno; Yuli Fatmawati (CV. ADIBA AISHA AMIRA, 2023)
This research focuses on the implementation of Muhadharah activities in improving the talents of students at the Madinatul Munawwarah Islamic boarding school. The purpose of this research is to determine the implementation of Muhadharah activities in improving the talents of students at Madinatul Munawwarah Islamic Boarding School. This research methodology uses a qualitative approach. The data obtained in this research was through interview observations and documentation studies. And based on the data obtained, the analysis researcher used descriptive analysis, namely by describing or illustrating how Muhadharah Activities are Implemented in Increasing the Talents of Santri at the Madinatul Munawwarah Islamic Boarding School. The results of this research are that muhadharah activities have a very important role in developing students' talents. Based on the results of research in the field, researchers obtained several findings, including that muuhadhoroh activities are routinely carried out every Friday at 07.00 WIT until finished, muhadhoroh activities must be carried out by each representative of each scheduled class. Apart from that, there are many benefits for students after taking part in these muhadhoroh activities, namely increasing their talent and confidence in speaking in public.